A study of haemoglobin percentage among pregnant woman at first visit in antenatal clinic in South Dumdum Municipal hospital, Kolkata - Mondal, Chaitali; Panti, Riyanka (International Journal of Research in Medical Sciences, 2021)
Background: Low maternal haemoglobin concentrations during pregnancy have been reported to increase risk of small for gestational age (SGA) birth, which is a predictor of stillbirth. The objective was to find out a study of Hb% among pregnant woman. Methods: All consenting of 200 pregnant woman attending antenatal clinic in the department of obstetrics and gynaecology at South Dumdum municipal hospital, Dumdum, Nager Bazar, Kolkata were included in the study. Results: Out of 200 pregnant woman, 75 woman were anaemic and there average Hb% was 10.10 and 125 mothers were non-anaemic and their average Hb% was 11.61. 39 mothers whose parity p0+0 and avg. Hb%-11.305 out of them 10 mothers are anaemic. In contrast 73 mothers whose parity P0+1 and average Hb% was 23.860, out of them 30 mothers were anaemic. In contrast 5 mothers whose parity P0+2 and average Hb% was 10.76, out of them 0 mother was anaemic. In contrast 22 mothers whose parity P1+0 and average Hb% was 10.31, out of them 13 mothers were anaemic. In contrast 56 mothers whose parity P1+1 and average Hb% was 11.31, out of them 19 mothers were anaemic. In contrast one mother whose parity P1+2 and average Hb% was 0.2 and she was anaemic. In contrast one mother whose parity P2+0 and Hb% was 10 and she was anaemic. In contrast two mothers whose parity were P2+1 and Hb% was 9.55 and out of them one mother was anaemic. In contrast one mother whose parity is p3+1 and Hb% was 12. Conclusions: Out of 200 pregnant woman 75 were anaemic and 125 woman were non-anaemic.